Distinct alterations of fecal microbiota refer to the efficacy of adalimumab in Crohn's disease - Liang Chen; Zhanjun Lu; Dengfeng Kang; Zhongsheng Feng; Gengfeng Li; Mingming Sun; Zhanju Liu; Wei Wu; Leilei Fang (Frontiers Media S.A., 2022)
Background and Aims: Anti-tumor necrosis factor mAb (i.e., adalimumab, ADA) is currently used in the treatment of patients with Crohn's disease (CD). However, its regulation on fecal microbiota is still not fully understood.Methods: A retrospective analysis was conducted on 115 patients with CD who received treatment with ADA for 12 weeks at the Inflammatory Bowel Disease Center in Shanghai Tenth People's Hospital and Department of Gastroenterology in Shanghai General Hospital. The Crohn's disease activity index (CDAI) evaluation was applied to patients before ADA therapy at week 0, 4, 8, and 12. Clinical remission (CR) was defined as the CDAI < 150. All patients underwent ileocolonoscopy or enteroscopy at baseline (week 0) and week 12. Crohn's Disease Endoscopic Index of Severity (CDEIS) scores were calculated by two experienced physicians to assess endoscopic activity. Mucosal healing (MH) was assigned a CDEIS score between 0 and 3. Fecal samples were collected from eight CD patients at baseline and week 12, and the microbiota was analyzed by using 16S RNA sequencing.Results: At week 12, CR was achieved in 70.6% (72/102) of the patients with active CD. A total of 47.1% (48/102) of the patients with active CD attained MH, among which, 56.6% (30/53) of the patients with mildly active CD (3 ≤ CDEIS <9) and 48.0% (12/25) of the moderately active CD patients (9 ≤ CDEIS <12) attained MH, but only 25.0% (6/24) achieved MH in severely active CD patients (CDEIS ≥12). The efficacy of ADA was not associated with lesion locations (χ2 = 0.409, p = 0.815). Unexpectedly, we found an increase in protective microbiota at the genus level (e.g., Barnesiella, Anaerostipes, Tyzzerella, Lachnoclostridium, and Lachnospiraceae_unclassified) but a decrease in pathogenic bacteria (Escherichia-Shigella) in fecal samples of the ADA-responsive group (ADA-R) when compared with those in the ADA-nonresponsive group (ADA-NR). Notably, the gene bglX coding β-glucosidase and gph encoding phosphoglycolate phosphatase were enriched in fecal samples of ADA-R. Conversely, the abundance of genes coding ATP-binding cassette (ABC) transporter system proteins was significantly enriched in fecal samples of ADA-NR when compared with that of the ADA-R.Conclusion: This study reveals that ADA markedly improves clinical remission and induces MH in mildly to moderately active CD patients and that distinct changes in the gut microbiota can be used to predict the efficacy of ADA.